Hematological consequences of pandemic influenza H1N1 infection: a single center experience - Unal, Sule; Gökçe, Müge; Aytaç-Elmas, Selin; Karabulut, Erdem; Altan, Ilhan; Ozkaya-Parlakay, Aslinur; Kara, Ateş; Ceyhan, Mehmet; Cengiz, Ali Bülent; Tuncer, Murat; Cetin, Mualla; Gümrük, Fatma (The Turkish Journal of Pediatrics, 2010)
Since its identification in April 2009, pandemic influenza H1N1 virus has affected thousands of people worldwide. Viruses, particularly Epstein-Barr virus, cytomegalovirus and parvovirus B19, may have diverse hematological consequences, including anemia, neutropenia, thrombocytopenia, lymphocytosis, hemophagocytic lymphohistiocytosis, and coagulation abnormalities. In this study, a total of 31 consecutive pediatric patients, with and without chronic diseases, who had flu symptoms and were confirmed to have pandemic influenza, were evaluated for hematological consequences upon presentation to hospital. Eight (25.8%) patients had leukopenia and six (19.4%) had thrombocytopenia at the time of diagnosis of H1N1 infection. Pandemic influenza H1N1 infection may cause diverse hematological findings, including cytopenias and hemophagocytosis.